A role for the androgen receptor in the treatment of male breast cancer. (February 2016) - Zhu, Jason; Davis, Carter T.; Silberman, Sandra; Spector, Neil; Zhang, Tian
Highlights: While male breast cancer is rare, AR is expressed in approximately 50% of all cases. When present, AR can be a therapeutic target, via AR-antagonists and GnRH agonists. Combination letrozole–leuprolide can result in durable responses for AR+ breast cancer. Abstract: Male breast cancer (BC) is relatively rare, making up less than 1% of all breast cancer cases in the United States. Treatment guidelines for male BC are derived from studies on the treatment of female BC, and are based molecular and clinical characteristics, such as hormone receptor positivity. For female estrogen receptor positive (ER+) breast cancers, the standard of care includes three classes of endocrine therapies: selective estrogen receptor modulators, aromatase inhibitors, and pure anti-estrogens. In contrast to female ER+ breast cancers, there is less known about the optimal treatment for male ER+ BC. Furthermore, in contrast to ER, less is known about the role of the androgen receptor (AR) in male and female BC. We report here the treatment of a 28-year-old man with metastatic AR+, ER+ breast cancer otherwise refractory to chemotherapy, who has had a durable clinical response to hormonal suppression with the combination of aromatase inhibition (Letrozole) in conjunction with a GnRH agonist (Leuprolide).